2013
DOI: 10.1116/1.4817178
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al/TiN/SiO2 structure on MOS capacitor, Schottky diode, and fin field effect transistors devices

Abstract: Titanium nitride (TiN) films were tested for their suitability as upper electrodes in metal–oxide–semiconductor (MOS) capacitors and Schottky diodes and as metal gate electrodes in fin field effect transistor devices. TiOxNy formation on TiN surfaces was confirmed by x-ray photoelectron spectroscopy and appears to be associated with exposure of the metal electrodes to ambient air. In order to avoid the formation of TiOxNy and TiO2, a layer of aluminum (Al) was deposited in situ after the TiN deposition. TiN wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…Thus, minimum unsaturated bonds exist at the interface. Lima et al [27] showed that Al/TiN is suitable to use for complementary metaloxide-semiconductor devices.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, minimum unsaturated bonds exist at the interface. Lima et al [27] showed that Al/TiN is suitable to use for complementary metaloxide-semiconductor devices.…”
Section: Reviewmentioning
confidence: 99%
“…Thus, minimum unsaturated bonds exist at the interface. Lima et al [27] showed that Al/TiN is suitable to use for complementary metaloxide-semiconductor devices.Kaufmann et al [28] studied the SiC Schottky diode as a particle detector. The authors fabricated Schottky junctions by depositing dielectric HfO 2 and TiO 2 insulating layers using atomic layer deposition onto a silicon carbide substrate.…”
mentioning
confidence: 99%
“…22,23 An aluminum cap layer is deposited by DC sputtering to reduce the gate stack series resistance and to avoid further incorporation of oxygen in the TiN electrode in the postprocessing steps. 9 The gate last integration scheme was employed to prevent parameter shifts in the TiN electrode after high temperature annealing. 24,25 Self-alignment using chemical-mechanical planarization step is still being calibrated in our lab, which impacts our design choices.…”
Section: B Finfet Device Fabricationmentioning
confidence: 99%
“…11,12 Focused ion beam (FIB) for device fabrication has two main approaches: milling and lithography. While several works have been carried out using milling and ion-assisted material deposition for transistor fabrication, [7][8][9]13,14 here we explore a maskless and resistless lithography method for nanoscale multiple fin definition, which is used for FinFET prototype fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Variations on TiN properties have been reported for different deposition processes. 7 Several techniques such as chemical vapor deposition (CVD), physical vapor deposition (PVD), and sputtering have been investigated for obtaining TiN films. Nowadays, atomic layer deposition (ALD) system is being widely used for TiN deposition due to the requirement of conformal layers for 3D channel structures, like tri-gates and finFET's.…”
Section: Introductionmentioning
confidence: 99%